(untitled) - Chadarevian, Soraya de. (Cambridge, UK, 2002)
Molecular biology has come to dominate our perceptions of life, health and disease. In the decades following World War II, the Medical Research Council Laboratory of Molecular Biology at Cambridge was a world-renowned center of this emerging discipline. Crick and Watson, among others, did the work that made them famous in this laboratory. Soraya de Chadarevian's important new study is the first to examine the creation and expansion of molecular biology and its place on the postwar governmental agenda through the prism of this remarkable institution.
Keywords: Molecular biology,Sinh học phân tử; History,Lịch sử; 20th century,thế kỷ 20; Great Britain|y,Nước Anh